Advanced Virtual Monoenergetic Computed Tomography of Hyperattenuating and Hypoattenuating Liver Lesions: Ex-Vivo and Patient Experience in Various Body Sizes. Issue 10 (October 2015) - Husarik, Daniela B.; Gordic, Sonja; Desbiolles, Lotus; Krauss, Bernhard; Leschka, Sebastian; Wildermuth, Simon; Alkadhi, Hatem
Abstract : Objective: To determine the value of advanced virtual monoenergetic images (mono+) from dual-energy computed tomography (CT) of hyperattenuating and hypoattenuating liver lesions in various phantom sizes and patients in comparison with standard monoenergetic images (mono). Materials and Methods: Anthropomorphic phantoms simulating 4 patient sizes (S, 300 × 200 mm; M, 350 × 250 mm; L, 400 × 300 mm; and XL, 600 × 450 mm) with a liver insert containing both hyperattenuating and hypoattenuating iodine-containing lesions were imaged with dose-equivalent dual-energy (100/150 Sn kilovolt [peak] [kVp]) and single-energy (120 kV[p]) protocols on a 192-slice dual-source CT system. In addition, 4 patients with 3 hypoattenuating and 3 hyperattenuating hepatocellular carcinoma were included and underwent dual-energy CT imaging with the same scanner at similar kV(p) settings (100/150 Sn kV[p]). Images were reconstructed with standard mono and with the mono+ algorithm at 10–kiloelectron volt (keV) intervals from 40 to 190 keV. Attenuation of the liver and lesions were measured, and contrast-to-noise ratios (CNRs) were calculated. Lesion conspicuity was rated by 2 blinded independent readers in all mono and mono+ data sets from 40 to 190 keV using a 5-point Likert scale (1, lowest conspicuity; and 5, highest conspicuity). Results: Attenuation in the liver and in both hyperattenuating and hypoattenuating lesions did not differ between mono and mono+ ( P = 0.41–0.49). Noise on mono+ was significantly lower than on mono for all phantom sizes ( P < 0.05) and was increasing with phantom size. Hyperattenuating lesion CNR was highest for mono+ images at 40 keV in the S phantom (6.73), with significantly higher CNR for mono+ than for mono and for single energy (120 kV[p]) in all phantom sizes (all P < 0.001) except for the XL phantom. Hypoattenuating lesion CNR was highest for high-keV mono+ being significantly higher than on mono and on single-energy (120 kV[p]) images (all P < 0.001), except for the XL phantom with significantly higher CNR for mono (1.3) compared with mono+ (0.47) and 120 kV(p) (1.26). In patients, CNR curves of hyperattenuating hepatocellular carcinoma were in accordance with the phantom data, whereas hypoattenuating lesions demonstrate varying curves, some being in accordance with findings in phantoms. Interreader agreement for lesion conspicuity was very good (intraclass correlation, 0.95), with higher conspicuity scores for mono+ than for mono and single energy (120 kV[p]) at all phantom sizes (all P < 0.05) and within patients. Conclusion: Our ex vivo and patient data demonstrate added value for imaging of both hyperattenuating and hypoattenuating liver lesions with advanced virtual monoenergetic dual-energy CT by decreased noise, increased CNR, and higher lesion conspicuity, although with limitations in XL body sizes.